2019
DOI: 10.1002/ijc.32825
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of rare coding variants in OGDHL and BRCA2 in relation to breast cancer risk in Chinese women

Abstract: The missing heritability of breast cancer could be partially attributed to rare variants (MAF < 0.5%). To identify breast cancer‐associated rare coding variants, we conducted whole‐exome sequencing (~50×) in genomic DNA samples obtained from 831 breast cancer cases and 839 controls of Chinese females. Using burden tests for each gene that included rare missense or predicted deleterious variants, we identified 29 genes showing promising associations with breast cancer risk. We replicated the association for two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 39 publications
(86 reference statements)
0
5
0
Order By: Relevance
“…Gene-expression and whole-genome sequencing data from these samples were processed according to the GTEx protocol, as described in our previous work. [39][40][41] For gene-expression data, expression levels of each gene have been measured using reads per kilobase per million units from RNA-SeQC. We performed data quality control and normalization processing by filtering lowly expressed genes, log2 transforming, and Robust Multichip Average.…”
Section: Gene-expression Model Building Using Genotype-tissue Expressionmentioning
confidence: 99%
“…Gene-expression and whole-genome sequencing data from these samples were processed according to the GTEx protocol, as described in our previous work. [39][40][41] For gene-expression data, expression levels of each gene have been measured using reads per kilobase per million units from RNA-SeQC. We performed data quality control and normalization processing by filtering lowly expressed genes, log2 transforming, and Robust Multichip Average.…”
Section: Gene-expression Model Building Using Genotype-tissue Expressionmentioning
confidence: 99%
“…The median sequence read depth was − 50X. The processing of the sequencing data has been previously described [23][24][25]. Briefly, paired-end reads were aligned to the human genome reference hg19 using BWA (version 0.75).…”
Section: Whole-exome Sequencing and Quality Controlmentioning
confidence: 99%
“…OGDHL overexpression and knockdown studies have shown that OGDHL inhibits cell growth and migration by inactivating ATK signaling 56 . Moreover, a recent study revealed that rare variants of OGDHL were significantly correlated with breast cancer in a Chinese cohort 57 , and its association with parathyroid carcinoma is also worth considering. Second, carcinoma-specific gene expression or repression suggests the underlying molecular mechanisms of tumor progression (Fig.…”
Section: Discussionmentioning
confidence: 99%